Professional bodies’ perspectives on corruption definitions, risks and mitigation in the Malaysian built environment sector - Rabe, Noor Suzilawati; Abdullah, Muhammad Faris; Hashim, Khairusy Syakirin Has-Yun; Ab Sani, Jasasikin; Sapian, Abdul Razak; Ibrahim, Izihan; Mohd Abbas, Abazazilah (IIUM Press, 2025)
The built environment sector is central to Malaysia’s national the built environment sector is a critical driver of Malaysia’s economic growth and societal development, yet it is widely recognised as highly susceptible to corruption. This study examines corruption risks and mitigation strategies within the sector from the perspective of professional bodies. Employing a qualitative approach, semi-structured interviews were conducted with six senior representatives from key professional bodies, which were the Board of Architects Malaysia, Board of Engineers Malaysia, Board of Quantity Surveyors Malaysia, Land Surveyors Board, Board of Town Planners Malaysia, and the Institute of Landscape Architects Malaysia. Participants were selected based on their extensive professional experience and positions of authority within their organisations, ensuring informed insights on governance, ethics, and sectoral practices. Findings indicate that corruption is multi-dimensional, occurring at all stages in the built environment, from tendering to construction and post-contract compliance. Tendering was identified as the stage most prone to integrity risks, driven primarily by large financial transactions, procedural ambiguities, and social pressures. While respondents believe that professionals are generally not the main actors in corrupt practices, they operate within a system that can enable misconduct, highlighting the importance of ethical awareness and institutional guidance. Professional bodies play a crucial role in promoting integrity, through mechanisms such as ethics-based examinations, professional development programmes, whistleblower policies, and collaborative initiatives with the Malaysian Anti-Corruption Commission. Despite their limited statutory authority, these bodies contribute significantly to safeguarding public interest and reinforcing ethical standards. The study concludes that effective corruption mitigation by the professional bodies requires integrated governance across project stages, strengthened professional ethics, and continuous collaboration between professional bodies and regulatory authorities. These findings provide practical implications for policymakers, professional bodies, and practitioners, offering insights into corruption risks and strategies to enhance transparency, accountability, and professional integrity in Malaysia’s built environment sector.